Refurbishing occupied buildings the management of risk under the CDM regulations - Nutt, Bev (Thomas Telford, 1998)
Based around the CDM regulations, this guide draws information from Health and Safety Executive data, to develop a profile of construction activities, enabling readers to identify and prioritise health and safety risks during the refurbishment of occupied buildings.
Keywords: Buildings -- Repair and reconstruction -- Safety measures.; elektronické knihy; electronic books